Presidential Decree No. 76/2013 On the Amendment of Some Provisions of Law No. 96/1996 on the Regulation of Press - egypt (2025)
Presidential Decree-Law No. 76 of the year 2013 on the amendment of some provisions of law no. 96 of the year 1996 on the regulation of press – قرار رئيس جمهورية مصر العربية بالقانون رقم 76 لسنة 2013 فى شأن تعديل بعض أحكام القانون رقم 96 لسنة 1996 بشأن تنظيم الصحافة